A systematic review of China's outbound tourism research. Issue 12 (12th December 2016) - Law, Rob; Sun, Sunny; Fong, Davis Ka Chio; Fong, Lawrence Hoc Nang; Fu, Hui
Abstract : Purpose: This paper aims to identify the changes of researched destinations along with the Approved Destination Status scheme to investigate the development of research problems, and to track the changes of research topics in the context of the development of China's outbound tourism. The research methods and applied theories are also identified and analyzed. Design/methodology/approach: Three large databases, namely, ScienceDirect, EBSCOhost and Google Scholar, were selected to search for published articles (i.e. 107 empirical articles and 15 review/policy articles) related to China's outbound tourism. Thereafter, the retrieved articles were categorized and analyzed. Finally, a theoretical framework was provided for future studies on China's outbound tourism. Findings: The major findings indicated that the main topics related to China's outbound tourism included market segmentation, travel motivation and travel behavior. One or two theories are generally applied to investigate a certain topic. The most common research methods are interviews and a questionnaire survey. Research limitations/implications: Future studies are suggested to apply more theories to investigate one topic. A single theory can also be applied to investigate different topics. Adopting different and innovative research methods, such as online interaction observation, can also be considered. Originality/value: This study contributes to the literature through an in-depth qualitative assessment of China's outbound tourism literature, comparing researched destinations with the Approved Destination Status policies, and reviewing articles based on research.